Hydroboration of alkynes and nitriles using an α-diimine cobalt hydride catalyst. Issue 53 (15th May 2017) - Ben-Daat, Hagit; Rock, Christopher L.; Flores, Marco; Groy, Thomas L.; Bowman, Amanda C.; Trovitch, Ryan J.
Abstract : The κ 4 -diimine cobalt hydride compound, ( Ph2PPr DI)CoH, has been found to catalyze E -selective alkyne hydroboration and the dihydroboration of nitriles. Abstract : Addition of NaEt3 BH to ( Ph2PPr DI)CoCl2 affords the corresponding monohydride, ( Ph2PPr DI)CoH. X-ray diffraction and DFT calculations indicate that this compound possesses a radical monoanion α-DI chelate and a Co(ii ) centre. Notably, ( Ph2PPr DI)CoH catalyzes the hydroboration of alkynes and dihydroboration of nitriles under mild conditions.